Chromosome-level genome assembly of a destructive leaf-mining moth Eriocrania semipurpurella alpina - Gui-fang Wang; Jin-wu He; Cheng Sun; Xue-yan Li; Pei-feng Qi; Dan-dan Feng; Cai-qing Yang; Ai-bing Zhang (Scientific Data)
Abstract Eriocraniidae (Lepidoptera) are widespread leaf miners and have unique adaptability to hypoxia and low temperatures, causing covert but devastating harm to Fagales (Betulaceae and Fagaceae) plants in the Holarctic. However, the lack of a high-quality genome of this most ancient family within the angiosperm-feeding group largely limits the studies on the phylogeny and environmental adaptation of the primitive Lepidoptera. In this study, utilizing Illumina sequencing, PacBio HiFi sequencing, and Hi-C technology, we constructed a chromosome-level genome assembly of E. semipurpurella alpina, representing the first high-quality genome in the Eriocraniidae family. The genome was 523.71 Mb in length, with a scaffold N50 of 17.55 Mb, and 95.56% of the assembly anchored onto 32 pseudochromosomes. BUSCO completeness values of 97.6%. 49.02% of the genome sequences were recognized as repetitive sequences, and a total of 22,581 protein-coding genes were annotated. This genome will greatly facilitate the phylogenomic studies of the most ancient lineages of Lepidoptera and provides insights into the genetic architectures underlying ecological adaptation.